Determinação do índice de disponibilidade de umidade para a Região Oeste do Paraná - Maggi, Cacea Furlan (2006)
The objective of the present study compare the models of estimation of evapotranspiration of Reference (ETo) was adjusted of probabilistic Gama, Lognoral, and generalization distribution of extreme value, solver behind of Camargo, on Paraná West and to determine the wet availability index. The dados was obtained in IAPAR (Paraná Institute Agronomy) end SIMEPAR (Paraná Meteorology System). Worked of medium month temperature dados of Paraná regions, with geographic localization 24º14 00 latitude S to 25º27 00 and 53º07 00 to 54º24 00 longitude W far from Greenwch. The historic series done showed dados of 6 to 32 year of month medium temperature. The month medium temperature was used for solver of ETo. With of month dados was adjusted of probabilistic models associate of 75% occur. For to tried of probabilistic Gama and Lognormal models was to used adherences test of Kolmogorov-Smirnov, with 5% of probability. For GEV distribution of qualify of adjusted was available of Wang test of 5% probability. This values of P75 was used for wet availability index. The result was probabilistic Gama and Lognormal model showed similar comportment with to estimative of ETo, therefore all 144 series studied was accept of Kolmigorov-Smirnov adherence test, until of station with a few year of register adjusted, consequently the two models adjusted correct the ETo dados. The GEV model of 144 series available, 22 don t was accept of Wang test of 5% probability. On wet availability index showed variation of 0.33 to 1.33, how reference for wet availability analyses that valor less of 0.33 are to point out of deficit end tall of 1.33 wet excess. The results showed of June was the month the most valor of IDUs, was in this month too of occur better station number with wet excess, the 12 station available, 8 showed wet excess in this month. Was possible do see the most valor os IDUs happened in regions next, in São Miguel do Iguaçu and Foz do Iguaçu. All the series available don t shoed wet deficit.